2020
DOI: 10.1038/s41598-020-70130-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic nomogram for elderly patients with acute respiratory failure receiving invasive mechanical ventilation: a nationwide population-based cohort study in Taiwan

Abstract: Patients in critical care medicine are ageing. There is limited literature evaluating long-term outcomes and prognostic factors for the growing number of elderly patients with acute respiratory failure (ARF) receiving invasive mechanical ventilation (IMV). Data on elderly patients (≧ 65 years old) with ARF receiving intubation and IMV during 2003–2012 were retrospectively collected from the national health database in Taiwan. We included 7,095 elderly patients. The 28-day mortality was 33%, the 60-day mortalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
(41 reference statements)
1
8
0
Order By: Relevance
“…The outcome of AHRF in our study was similar to what was reported in the same period in several cohorts of mechanically ventilated hypoxaemic patients [10,17,18]. However, the observed mortality was almost 10% higher compared to cohorts in Italy and in Canada with similar demographics and similar degrees of hypoxaemia [19,20].…”
Section: Discussionsupporting
confidence: 89%
“…The outcome of AHRF in our study was similar to what was reported in the same period in several cohorts of mechanically ventilated hypoxaemic patients [10,17,18]. However, the observed mortality was almost 10% higher compared to cohorts in Italy and in Canada with similar demographics and similar degrees of hypoxaemia [19,20].…”
Section: Discussionsupporting
confidence: 89%
“…Intracranial haemorrhages are associated with very high rates of mortality or severe impairment in this age group 31 . Respiratory failure, the most common medical cause for unconsciousness in older individuals, often marks the final stage of morbidity and is thus associated with high mortality rates 32 . This shift seems to be relevant with regards to the decision-making processes and the suspected cause of unconsciousness.…”
Section: Discussionmentioning
confidence: 99%
“…Only 3 out of 10 elderly patients admitted to the ICU, both with acute respiratory failure and using mechanical ventilation, survived in one-year observation. 15 The mechanism causing this is diffuse alveolar damage. Several aetiologies such as cytokine-laden pneumonia, aspiration, direct injury by ventilation pressure may cause profound uid and cellular exudation.…”
Section: Discussionmentioning
confidence: 99%